SDC1 knockdown induces epithelial–mesenchymal transition and invasion of gallbladder cancer cells via the ERK/Snail pathway. Issue 8 (August 2020) - Liu, Zixiang; Jin, Hao; Yang, Song; Cao, Haiming; Zhang, Ziyan; Wen, Bo; Zhou, Shaobo
Background: Expression levels of the cell adhesion molecule syndecan-1 (SDC1) have been shown to be inversely proportional to tumor differentiation and prognosis. However, its role in the development of gallbladder cancer (GBC) remains unclear. Methods: We knocked down SDC1 in GBC cells by RNA interference and determined its roles in cell proliferation, apoptosis, invasion, and migration by Cell Counting Kit-8, colony-formation, flow cytometry, Hoechst 33342 staining, transwell invasion, and scratch wound assays. Expression levels of epithelial–mesenchymal transition (EMT)-related and extracellular signal-regulated kinase (ERK)/Snail pathway proteins were determined by western blotting and immunofluorescence. Results: Cell proliferation, invasion, and migration were all increased in GBC cells with SDC1 knockdown, compared with cells in the blank control and negative control groups, but apoptosis was similar in all three groups. E-cadherin and β-catenin expression levels were significantly lower and N-cadherin, vimentin, p-ERK1/2, and Snail expression were significantly higher in the SDC1 knockdown group compared with both controls, while ERK1/2 levels were similar in all groups. Reduced E-cadherin and increased vimentin levels were confirmed by immunofluorescence. Conclusions: SDC1 knockdown promotes the proliferation, invasion, and migration of GBC cells, possibly by regulating ERK/Snail signaling and inducing EMT and cancer cell invasion.